Case Report: Subcapsular hematoma post-transarterial embolization and its laparoscopic resolution - Yi, Haizhao; Wang, Qi; Bai, Xuecong; Liu, Jinlong; Fu, Hua (Frontiers in Medicine, 2026)
BackgroundHepatic hemangioma (HH) is a common benign liver tumor. Transarterial embolization (TAE) is a widely adopted minimally invasive treatment. Subcapsular hematoma (SCH) is an exceptionally rare and severe complication following TAE, with only sporadic cases reported and no standardized management protocol.Case presentationA 43-year-old female presented with acute right upper quadrant pain 8 days after an attempted TAE for a caudate lobe HH at another institution, which had been aborted due to unsuccessful vessel cannulation. Upon admission, contrast-enhanced CT revealed a large SCH in the right hepatic lobe alongside the known caudate lobe HH. Her condition rapidly deteriorated, with a significant decline in hemoglobin and signs of hemorrhagic shock, necessitating emergency intervention. She subsequently underwent a simultaneous laparoscopic procedure consisting of evacuation of the massive SCH (approximately 2000 mL) and enucleation of the giant caudate lobe hemangioma. The surgical strategy included a left-sided approach, utilization of the Arantius ligament as a key anatomical landmark, and low central venous pressure (CVP) anesthesia to minimize intraoperative bleeding.ConclusionThis case represents, to our knowledge, the first report of SCH as a complication following hepatic artery angiography or attempted TAE and the only reported case of simultaneous laparoscopic management of both a ruptured SCH and a caudate lobe HH. It highlights that SCH, although rare, can be a life-threatening complication of endovascular procedures. Laparoscopic surgery is a feasible and effective therapeutic option for managing such complex conditions. This report underscores the critical importance of meticulous technique during TAE and vigilant postoperative monitoring to prevent this serious complication.